Variation in Karnal bunt and powdery mildew resistance among somaclones and doubled haploids of bread wheat cv Sonalika - and R. S. CHAUHAN, K. D. SHARMA, B. M. SINGH (Indian Phytopathology, 2002)
Somaclones and doubled haploids of bread wheat cv. Sonalika were regenerated from callus cultures derived from immature embryos and anthers and MS medium supplemented with 1.5 mg/litre 2,4-D and on potato-2 medium supplemented with 1.5 mg/litre 2,4-D, 0.5 g/litre glutamine and 9% sucrose. Calli derived from immature embryos were differentiated into shoots and roots on MS medium containing BAP and IBA at 1.5 mg/litre each and those from anthers were regenerated on potato-2 medium supplemented with 0.5 mg/litre IBA and BAP each. Regenerants from both the explants were evaluated for resistance to Karnal bunt (Neovossia indica [Tilletia indica]) and powdery mildew (Erysiphe graminis f.sp. tritici) under greenhouse conditions in R0 and R1 generations.One somaclone (no. 150) exhibited resistance to Karnal bunt infection in both the generations. However, 1 somaclone and 1 doubled haploid, which were free from Karnal bunt in the R0 generation, became susceptible in the R1 generation. Somaclone no. 150 and 1 doubled haploid (no. A22) were resistant to powdery mildew at the adult plant stage, with 1.9% and 1.4% disease severities on flag leaves, and 2.4% and 1.5% disease severities on second leaves, respectively, in the R1 generation. This compared with Sonalika wheat which had 24% and 38% powdery mildew severity on the flag leaf and second leaf, respectively.